Modeling the decision-making procedure for financing cybersecurity funds in the information and educational environment of the university - Кидираліна, Лазат Муктаровна; Ахметов, Бахитжан Сражатдіновіч; Лахно, Валерій Анатолійович (Ukrainian Information Security Research Journal, 2018)
The article proposes a model for evaluation of investment strategies in the information and educational environment of the University (IOCC). One of the options for solving such problems, and, in particular, assessing the risks associated with the financing of information security systems and cyber security of IOCC, is the implementation of intelligent decision support systems. Such systems allow the management of educational institutions to make rational decisions on investing financial resources in the development of the IOCC protection tools. The article proposes a model for the IDSP for a discrete procedure for financing the information protection and cyber security systems of the IOCC. Difference of the model from existing ones is the assumption of limited financial resources as the protection side of IOCC and attackers. The model is based on the use of the tools of the theory of multi-step games. The article describes the solution of a bilinear multistep game of quality with dependent motions within the framework of IOCC protection strategies. The results of the simulation experiment within the framework of the choice of financial strategies for cyber defense of IOCC are described. The developed intellectualized decision support system (IDSP) will allow the user to evaluate financial strategies when the investment directions in the information and cyber security information systems of the IOCC are aligned. Unlike existing models, a bilinear multistep game of quality in a class of pure strategies has been solved, and it makes it possible to assess the risks for players who accordingly represent the sides of defense and attack for IOCC. Various ratios of the parameters describing the financing process in the information protection and cyber security protection facilities of the IOCC were taken into account. In the course of the simulation experiment based on the results of the simulation experiment and the test results of the IDSP, a conclusion was made about the risks of loss of financial resources for players, respectively, by means of cyber defense and hacking the IOCC.